Study on loudspeaker system - Norazilah, Mohd Yusof (1997)
The loudspeaker is one of the device that exist in electronic equipment that normally used in radio receiver set, television, etc, that changes electrical impulses into audible sounds. Although all the speaker do the same things, which reproduce sound from electrical signals, indeed, not all the speakers are designed alike. There are different sizes, types and functions of speaker and made with a variety of materials. The designs also depend on the cost and the requirement nowadays. This project purposely to study and briefly explaining the operating of loudspeaker system. Through this project, it will concern about how speaker work according to its types and the elements required in building loudspeaker system such as the drivers and enclosures. In addition, it will shortly mention the using of computer program to design loudspeaker